2019
DOI: 10.1177/0145445519833041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acceptance and Commitment Therapy on Impulsive Decision-Making

Abstract: This study examined the transdiagnostic effect of acceptance and commitment therapy (ACT) on impulsive decision-making in a community sample. A total of 40 adults were randomized to eight individual sessions of ACT or an inactive control. Participants completed pre-, mid-, and post-assessments for psychological symptoms; overall behavior change; valued living; delay discounting; psychological flexibility; and distress tolerance. Data were analyzed with multilevel modeling of growth curves. Significant interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 113 publications
(163 reference statements)
1
7
0
Order By: Relevance
“…In this study, ACT in 8 sessions of 60 minutes reduced impulsivity and its three dimensions in rehabilitated MUD patients. Despite the low number of studies on the effect of ACT on impulsivity of MUD patients, it can be said that the results of the present study are consistent with the results of Morrison et al [22], Gomez et al [23], Nadimi [24], Borjali et al [25] and Aazam et al [26]. They reported that the third-wave behavioral therapies, including ACT, could effectively reduce impulsivity and impulsive behaviors.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, ACT in 8 sessions of 60 minutes reduced impulsivity and its three dimensions in rehabilitated MUD patients. Despite the low number of studies on the effect of ACT on impulsivity of MUD patients, it can be said that the results of the present study are consistent with the results of Morrison et al [22], Gomez et al [23], Nadimi [24], Borjali et al [25] and Aazam et al [26]. They reported that the third-wave behavioral therapies, including ACT, could effectively reduce impulsivity and impulsive behaviors.…”
Section: Discussionsupporting
confidence: 91%
“…One way to do this might be to work backwards from idiographic analyses, inductively identifying characteristics and generalizable processes that guide clinical decision making. A number of promising examples exist in the literature that orient to pathological processes that span across presentations and guide responses to particular procedures targeting particular processes (e.g., clinical perfectionism, impulsive decision BEYOND ACT: PBT 17 making; Egan et al, 2014;Fairburn et al, 2015;Gros, Szafranski, & Shead, 2017;Morrison et al, 2019;Newby, McKinnon, Kuyken, Gilbody, & Dalgleish, 2015).…”
Section: Researching Procedures Linked To Processesmentioning
confidence: 99%
“…Brief ACT training (60 to 90 minute sessions), that focused on promoting healthy decision making by training participants to observe emotions and to learn to act on values, rather than feelings, led to decreased delay discounting (Morrison, Madden, Odum, Friedel, & Twohig, 2014). On the other hand, ACT-based intervention applied to individuals with severe psychological problems, and targeting specific problem behaviors related to impulsive decision making and failed to decrease delayed discounting, when compared to a control group; however, it did help with reducing given problem behaviors (Morrison, 2016). To summarize, conclusions regarding the effectiveness of interventions based on mindfulness and psychological flexibility are promising, yet require further investigation.…”
Section: Mindfu Lness and Psychological Flexibility In Discountingmentioning
confidence: 99%